The language of covenant - Naylor, P (1980)
The centrality of covenant in the Hebrew scriptures has made it a theme of enduring significance. Accordingly, the language of covenant has acquired a corresponding importance. Whereas study of the language of covenant has not been neglected by scholars. the combination of impetus from ”Biblical Theology,” together with the tenets of traditional philology, has resulted in word-studies, which regard words as convenient labels for concepts. Some of the dangers of this approach have been exposed by Dr. James Barr, and, in the realm of New Testament Greek research, Dr. Nigel Turner has sought to explore the value of syntax and style. The present dissertation constitutes a determined attempt to discover the values of a similar approach to Biblical Hebrew semantics, in the restricted field of covenant language. If this approach has an appearance of being somewhat pedestrian, then that is due, in large part, to the absence of the kind of literature that facilitates the task of lexicography; the spadework of structural semantics is yet to be done, and the ground is fallow. The aim, therefore, is an articulation of the semantic structures of language associated with ברית. If any justification for this be required, then this writer's apology will be the same as Dr. Turner's: “my apology must be that the mechanics of speech provide a delicate and flexible means of communication which is worth scientific study.” Continued in theses ...